Clinical Guide Adaptation for Amalgam Waste Management in Dental Settings in Iran - Mahsa Eshrati; Fatemeh Momeniha; Nafiseh Momeni; Elham Ahmadi; Atieh Hashemian; Homa Kashani; Mojgan Alaeddini (Frontiers in Dentistry)
Objectives: Dental clinics are one of the major producers of mercury-containing waste due to the use of dental amalgam.  The atmospheric transport and persistence of mercury and its compounds in the environment, coupled with their high potential for bioaccumulation and detrimental effects on human health and ecosystems, underscore the necessity for effective management of mercury waste. Due to the lack of comprehensive and integrated guidelines for the effective management of dental amalgam waste in Iran, the objective of this study was to adapt a guideline for the management of amalgam waste in dental settings within the country.